Improving Students’ Critical Mathematical Thinking Skills Through SAVI Approach on Number Theory Lectures At Mathematics Education Department of Malikussaleh University - Marhami, Marhami; Rohantizani, Rohantizani; Nuraina, Nuraina (International Journal for Educational and Vocational Studies, 2020)
The research aimed to see whether SAVI learning approach is better than a normal class in improving students’ critical mathematical thinking skills due to number theory lectures of mathematics. This research used a quantitative research approach with experimental method in the form of quasi-experiment. The population of this research was all the fourth semester of mathematics department students of Malikussaleh University. The sampling used was a purposive sampling that consisted of students in class A1 and A2. The research design used a non –equivalent control group design. The instrument used in this research was a set of questionnaire of critical thinking that had been validated by several validators. Then, the analysis of the improvement score of students’ critical mathematical skills used a normalized gain data which shows the improvement of students’ score classification compared to the ideal maximum score. However, the n-gain score data of students’ critical mathematical skills of control class was not normally distributed. so a non-parametric test was conducted, namely the Mann Whitney U Test. Form Test results, the Asymp. Sig. (1-tailed) value was obtined around 0.008 < α = 0,05. This shows that H0 is rejected.Hence, it means that the improvement of students’ critical mathematical skills of experimental class is significantly better than a control class. Thus, it is also proven by the hypothesis that applying SAVI approach in learning is better than a normal class without any treatment in improving students’ critical mathematical thinking skills.